Management of biliary lithiasis in pregnancy – an updated overview - Corina Grigoriu; Catalin Lutic; Gina Calinescu; Consuela-Madalina Gheorghe; Andra Magdalena Balan; Tiberiu Augustin Georgescu; Vlad Dima; Radu-Mihai Grigoriu; Roxana Elena Bohiltea (Romanian Medical Journal, 2021)
It is estimated that 2% of pregnant women develop gallstones during pregnancy. Symptoms of biliary lithiasis may vary during pregnancy, from a slight added digestive discomfort to biliary colic of varying intensity, acute cholecystitis, or acute pancreatitis. Ultrasonography is the gold standard for diagnosis of sludge and gallstones, being both highly sensitive and specific. Initial management overlaps with the out-of-pregnancy management, initiating conservative, supportive care, as well as an adequate diet. Laparoscopic cholecystectomy is considered a safe intervention in pregnancy, being the second most common surgery after appendicectomy. If open laparoscopy is preferred, the major risk - perforation of the uterus - is avoided. Important complications of gallstones in pregnancy, jaundice and acute pancreatitis can be resolved safely and quickly by cholangiopancreatography (ERCP) techniques, with stone removal, sphincterotomy or stent mounting. After remission of pancreatic symptoms, laparoscopic cholecystectomy can be performed. Recent scientific data and current practice suggest an increase of biliopancreatic emergencies during pregnancy (probably due to rising incidence of obesity, age of gravida, prolonged use of oral combined contraceptives, dyslipidemia, etc.). Surgeons, as well as obstetricians, should be aware of the prompt modern management of these cases.